ANALISIS KADAR TIMBAL (Pb) DALAM DARAH DENGAN KARAKTERISTIK PETUGAS PENJAGA PINTU TOL (Studi Kasus di Gerbang Tol Waru Utama dan Waru Ramp Tahun 2015) - Zulia Hanin Nugraini; Hadi Suryono; Narwati . (Poltekkes Kemenkes Surabaya, 2015)
Motor vehicle exhaust gas consists of NOx, SOx, CO, lead (Pb) and Hydrocarbons. Toll gate keepersare at high risk of exposure to lead (Pb) from motor vehicle exhaust gas. The purpose of this studyis to determine blood lead level of toll gate keepers.This study is an observational study with cross-sectional approach. Population of the study was 97toll gate keepers and 30 of them were taken as samples. Samples were taken from both morningand afternoon shift. Data was taken through observation, measurement of lead (Pb) level in air andmeasured blood lead level of toll collectors.Results shows that most of the toll gate keepers were over 40 years old (93.3%). 29 collectors(96.7%) has employment period of more than 10 years. 15 Toll gate keepers (50%) wear PPE ontheir duty. Level of lead in the air has exceeded the TLV. Test results of blood lead levels showsnormal level in all workers.Conclusion asserts that toll gate keepers of over 40 years of age and 10 years of employment period showed higher average concentration of lead (Pb). Collectors wearing PPE on their duty showed higher average blood lead levels. It is recommended to the company to conduct trainingon dangers of lead in working environment to all tollgate keepers. Tollgate keepers are alsosuggested to always maintain their personal hygiene to avoid the influence of heavy metals lead(Pb) in the body.